A new IoT low-cost bi-directional wire extensometer for landslide monitoring - Cifaldi, Daniele; Mazza, Davide; Guadagno, Francesco Maria; Revellino, Paola (Frontiers in Earth Science, 2025)
The monitoring of slopes’ dynamics is essential to ensure the safety of infrastructures exposed to landslide risk and to develop mitigation strategies. However, it is not always possible to perform proper and slope-distributed monitoring due to the high cost of professional instruments. In this context, we developed a low-cost Arduino©-based wire extensometer for landslide monitoring. This instrument is capable of measuring the bi-directional distance between two fixed points, which is useful in landslide areas to observe linear displacements over time. Traditional wire extensometers are equipped with potentiometers, which allow measuring only finite displacements. Instead, our low-cost extensometer exploits a capacitive rotary encoder, which is able to measure infinite displacements. In addition, the new instrument can measure both wire lengthening and shortening, thanks to a spring-loaded winding system. Furthermore, the instrument’s settings can be modified to reach a millimetric resolution. The device - developed on an Internet of Things (IoT) project - is equipped with an online data transmission system and with a data-log system for local data storage. Laboratory and field tests were carried out with the aim of evaluating the instrument’s accuracy and reliability. Preliminary results demonstrate the great potential of this low-cost sensor for displacement measuring in the field of landslide monitoring.